On the horizon - Lowry, Lois (Clarion Books, 2022)
American author Lois Lowry writes about how her life in Hawaii intersected with the bombing of Pearl Harbor, her life in Tokyo after the war, and the lives that were lost in both the Pearl Harbor bombing and the nuclear bomb in Hiroshima.